PERAN GURU AGAMA KATOLIK DALAM PEMBENTUKAN KARAKTER KERUKUNAN DAN SOLIDARITAS SISWA (STUDI KASUS DI SMA ST. ANGELA BANDUNG) - Putri, Tresia Afila Eka; Midun, Hendrikus; Payong, Marselus Ruben (Bahasa Indonesia, 2025)
Pastoral activity is a form of Church service to the lives of the people. Harmony and solidarity are basic attitudes necessary to live in a pluralist community. These attitudes can create social cohesion between members of the school community. However, the implementation of these attitudes depends on the policies, pedagogical models and habits carried out in schools. This study aims to describe the roles, challenges and pedagogical efforts of Catholic Religious Education teachers to increase harmony and solidarity between students. This study uses a qualitative descriptive approach. The data collection methods are interviews, observations, and documentation. The research informants included school principals, PAK teachers, parents, and students. The results of the interview were analyzed using three steps, namely data reduction, data presentation, and conclusion. The results of the analysis found three points: 1) The Catholic religious education teachers have a direct and indirect role in efforts to increase harmony and solidarity between students; 2) The Catholic religious education teachers did not find any serious obstacles in the implementation of harmony and solidarity between students; Small obstacles occur when students have varied parents' economic backgrounds, so the process of adjusting students in school takes a relatively long time; 3) The Catholic religious education teachers' efforts to overcome obstacles to living in harmony and solidarity are to create a variety of activities that involve many students. Based on these findings, suggestions for improving the implementation of The Catholic religious education learning and further research are formulated.